2021
DOI: 10.3389/fphys.2021.678362
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal MicroRNA Transfer by Platelets – Evidence and Implications

Abstract: For decades, platelets have been known for their central role in hemostasis and their ability to release bioactive molecules, allowing inter-platelet communication and crosstalk with the immune system and vascular cells. However, with the detection of microRNAs in platelets and platelet-derived microvesicles (MVs), a new level of inter-cellular regulation was revealed. By shedding MVs from their plasma membrane, platelets are able to release functional microRNA complexes that are protected from plasma RNases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 120 publications
(154 reference statements)
0
9
0
Order By: Relevance
“…In recent years, it has been found that platelet-derived miRNAs can be released into the peripheral blood via encapsulation in PMPs ( 35 ). In contact with the neighboring cells, the internalized PMPs deliver miRNAs, which regulate the function of the recipient cell by post-transcriptional reprogramming ( 36 ). MiR-223, which is abundantly expressed in human platelets, is encapsulated in PMPs and released upon thrombin stimulation ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been found that platelet-derived miRNAs can be released into the peripheral blood via encapsulation in PMPs ( 35 ). In contact with the neighboring cells, the internalized PMPs deliver miRNAs, which regulate the function of the recipient cell by post-transcriptional reprogramming ( 36 ). MiR-223, which is abundantly expressed in human platelets, is encapsulated in PMPs and released upon thrombin stimulation ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…38–40 During their biogenesis, platelets are packaged with a finite quantity of megakaryocytic RNA, which following their release into the circulation is either translated, degraded or released. 41 , 42 Being anucleate, platelets are unable to transcribe new RNA and therefore RNA levels decline across platelet life span. This phenomenon has been well established and as such has allowed the monitoring of platelet turnover in patient groups through measurement of the immature platelet fractions within full blood counts.…”
Section: Omic Alterations In An Aged Plateletmentioning
confidence: 99%
“…In addition, the pharmacokinetics related to the time between drug administration and blood sampling need to be considered. Several studies to date aimed to identify an improved biomarker for cardiovascular risk stratification and assessment of platelet reactivity, among them miRNAs are currently becoming the centre of scientific attention [ 47 ]. Indeed, several correlations between miRNA concentrations and platelet reactivity have been found [ 36 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] ( Figure 2 ).…”
Section: Mirnas Expression and Platelet Reactivitymentioning
confidence: 99%